ANALYSIS OF IMPLEMENTATION OF PUBLIC SERVICE STANDARDS FOR MAKING KTP-EL (CARD ELECTRONIC IDENTITY) IN SIWALANKERTO VILLAGE WONOCOLO DISTRICT, SURABAYA CITY - Iswandany, Retno; Arianto, Agus; Waloyo (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
This study examines the implementation of public service standards for the issuance of the KTP-EL (Card Electronic Identity Card) in Siwalankerto Village, Wonocolo District, Surabaya City. With a focus on the efficiency, effectiveness, and overall quality of the service delivery process, the research investigates the extent to which the established public service standards are adhered to, identifying any gaps or challenges in the implementation process. Using a combination of qualitative and quantitative research methods, including interviews, surveys, and document analysis, the study aims to provide insights into the strengths and weaknesses of the current system and offer recommendations for improving the delivery of public services related to the issuance of the KTP-EL in the specified area. The findings of this research are expected to contribute to the enhancement of public service standards and the overall governance of administrative processes in Siwalankerto Village, as well as similar contexts in other regions